Estratégias da gestão turística de base comunitária em unidade de conservação: a arie da Vila do Estevão, Aracati-Ce - Takahashi, Saori (2016)
The study was developed in the Area of Relevant Ecological Interest (ARIE) of Estevão Village, located in the municipality of Aracati, State of Ceará, northeastern part of Brazil. The state represent an important tourist potential and intensive tourism, mainly because of the beautiful beaches with both on the national and international scale. The Estevão Village is located next to Canoa Quebrada, known as one of the most famous tourism destinations in the coastline of municipality of Aracati, located 13 km from the district headquarters and 179 km from Fortaleza, the capital state. The Village where the focus of this research has a characteristic similar to community based tourism. Both Canoa Quebrada and the the Village of Estevão develops different forms of tourism, highlighting the awareness and consciousness of the conservation of natural and cultural heritage of the community in the Estevão Village. The overall objective of this research was to develop the strategic planning of community based tourism, with the participation of local community in the ARIE of Estevão Village. Thus, this study aimed to contribute significantly to the development of a community based tourism in the ARIE of Estevão Village, using the precepts of Geoecology of landscapes, in order to promote a form of tourism that value the local cultures and the preservation and permanence of the natural resources of the environment. The main result of the study was the community's potential and limitations identified to develop the community tourism proposal, for the effective tourism based on the exist activities in the Village grounding inadequate environmental characteristics, social, cultural and economic through the research.